2018
DOI: 10.1016/j.bjm.2018.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Survey on pathogenic Escherichia coli and Salmonella spp. in captive cockatiels (Nymphicus hollandicus)

Abstract: We surveyed healthy captive cockatiels (Nymphicus hollandicus) for Escherichia coli and Salmonella spp. Cloacal swabs were collected from 94 cockatiels kept in commercial breeders, private residencies and pet shops in the cities of São Paulo/SP and Niterói/RJ (Brazil). Three strains of E. coli from each individual were tested for the presence of ExPEC-, APEC- and DEC-related genes. We evaluated the bla, bla, bla, bla, bla, tetA, tetB, aadA, aphA, strAB, sul1, sul2, sul3, qnrA, qnrD, qnrB, qnrS, oqxAB, aac (6)'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The bla KPC gene has already been reported among E. coli from different bird species belonging to the Columbiformes, Passeriformes, Charadriiformes, Accipitriformes, Falconiformes and Strigiformes orders [ 23 ]. In Brazil, Pontes et al [ 24 ] detected the resistance genes str AB, bla TEM, tet A, tet B, aad A, apha A, sul 1, sul 2, and sul 3 associated with plasmids in cloacal avian pathogenic Escherichia coli (APEC) strains from Nymphicus hollandicus in São Paulo and Rio de Janeiro. Cloacal E. coli from Pyrrhura griseipectus was phenotypically resistant to azithromycin, sulfamethoxazole-trimethoprim, streptomycin and tetracycline [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The bla KPC gene has already been reported among E. coli from different bird species belonging to the Columbiformes, Passeriformes, Charadriiformes, Accipitriformes, Falconiformes and Strigiformes orders [ 23 ]. In Brazil, Pontes et al [ 24 ] detected the resistance genes str AB, bla TEM, tet A, tet B, aad A, apha A, sul 1, sul 2, and sul 3 associated with plasmids in cloacal avian pathogenic Escherichia coli (APEC) strains from Nymphicus hollandicus in São Paulo and Rio de Janeiro. Cloacal E. coli from Pyrrhura griseipectus was phenotypically resistant to azithromycin, sulfamethoxazole-trimethoprim, streptomycin and tetracycline [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Horn et al (36) found that 55.7% of members of Enterobacteriaceae family isolated from canaries were MDR (36). Furthermore, Pontes et al (37) measured the total rate of MDR incidence in E. coli and salmonella spp. isolated from cockatiels to be 59% (37).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Pontes et al (37) measured the total rate of MDR incidence in E. coli and salmonella spp. isolated from cockatiels to be 59% (37). Regarding resistance against penicillin and erythromycin, both of which are common antibiotics for various human infections, 100% of STEC isolates in the study showed resistance, which should be considered an alarm.…”
Section: Discussionmentioning
confidence: 99%
“…In parrots from trafficking, Hidasi et al (2013) observed higher rates, as 23.5% of the samples were multiresistant to three antibiotic groups and 2.32% to four antibiotic groups. In captive cockatiels (an exotic species in Brazil), 30% of the isolates were resistant to seven or more antibiotics, and 59% of the strains were resistant to multiple drugs (Pontes et al 2018). The results of resistance to one or more antibiotics in free-living P. griseipectus may suggest that at some point, these birds have had contact with resistant strains or antibiotic residues in the environment, considering that these birds are not subjected to antibiotic therapy.…”
Section: Discussionmentioning
confidence: 99%